Advances in Design and Specification Languages for Embedded Systems
DOI: 10.1007/978-1-4020-6149-3_20
|View full text |Cite
|
Sign up to set email alerts
|

Reusing Systems Design Experience Through Modelling Patterns

Abstract: Voeten, J.P.M.; Verhoef, M.; Corporaal, H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…In this section we describe the state-of-the-art and related works that combine UML RTES with DSE as in [11] where modelling patterns to compose systems for DSE are presented or in [9]. In this last methodology, the analysis and synthesis tools available in the Metropolis framework [20] were used to support a DSE.…”
Section: State-of-the-art and Related Workmentioning
confidence: 99%
“…In this section we describe the state-of-the-art and related works that combine UML RTES with DSE as in [11] where modelling patterns to compose systems for DSE are presented or in [9]. In this last methodology, the analysis and synthesis tools available in the Metropolis framework [20] were used to support a DSE.…”
Section: State-of-the-art and Related Workmentioning
confidence: 99%
“…In the area of multi-media systems, [42] describes for example a case study performed in cooperation with Philips Research Laboratories Eindhoven on evaluating which mappings of a Picture-in-Picture application on a multi-processor system satisfied the performance requirements. [9] reports on a case study performed together with Chess Information Technology on evaluating the performance of alternative hardware architectures for executing an in-car navigation application by Siemens VDO. The latter two case studies not only provided valuable feedback to the designers of the considered systems, they also showed the feasibility of specialising the modelling and design fl ow of Figure 1 for a certain application domain.…”
Section: Industrial Case Studiesmentioning
confidence: 99%
“…In the area of high-tech systems, a case study in cooperation with ASML identified a crucial performance bottleneck in newly developed distributed control software for their wafer stepper system and also lead to a solution that satisfied the requirements. In cooperation with Océ Technologies, a new hardware design of a low-level control system in the next generation of printers has been investigated to confirm its feasibility [9]. As a final example, [16] describes a case study performed together with the University of Twente on real-time control software synthesis for part of a molding machine by Stork.…”
Section: Industrial Case Studiesmentioning
confidence: 99%
“…Building timed automata, VDM++ and POOSL models involves significantly more work than MPA and SymTA/S, although modeling templates were developed for POOSL to overcome this problem in part, see [35,37]. Furthermore, analysis takes more time and is in general not guaranteed to lead to deterministic results.…”
Section: Comparing the Modelsmentioning
confidence: 99%
“…Furthermore, other researchers have looked at different aspects of the case study, such as [35], [36], [12] or use different approaches to construct quantitative performance models, such as [34,37] and [33]. Last but not least, the comparison was continued with a significantly larger scope involving more case studies and additional tools in [81].…”
Section: Summary Of Research Contributionmentioning
confidence: 99%